Effects of Buckling-Restrained Braces on reinforced concrete precast models subjected to shaking table excitation. (15th May 2018) - Guerrero, Hector; Ji, Tianjian; Escobar, J. Alberto; Teran-Gilmore, Amador
Highlights: The effects of Buckling-Restrained Braces (BRBs) on precast, reinforced concrete (RC) models are examined. Shaking table tests were conducted on two four-storey frames, one with and one without BRBs, at a scale of 1/3. Several comparisons between the two models are presented to illustrate the benefits of the BRBs. The models were tested for two types of ground motion: low-intensity white noise, and a seismic motion taken on soft soil. The results show the benefits of BRBs: increase of damping and reduction of the seismic response and stiffness degradation. Abstract: To examine the effects of Buckling-Restrained Braces (BRBs) on precast, reinforced concrete (RC) models, shaking table experiments were conducted on two four-storey frames at a scale of 1/3. One model was without BRBs and designed according to common practice in Mexico (Model 1), while the other (Model 2) was equipped with BRBs and designed according to a displacement-based methodology. This paper presents several comparisons between the two models to illustrate the benefits of the BRBs. The fundamental frequencies, damping ratios and seismic response of the models were monitored. The models were subjected to two types of ground motion: low-intensity white noise, and the SCT-EW record of the M8.1 Michoacán earthquake of 19/09/1985 scaled to 50, 100, 150 and 200%. The most significant findings of this study were: (1) for the linear-elastic response, the BRBs increased the damping ratios significantly; and (2) improvements of the seismic response, due to the BRBs, were quantified in terms of several parameters. Retrofitting was also explored by replacing the BRBs in Model 2 after the original model had been subjected to the seismic tests.